Penggunaan Aditif Pakan Berbahan Alami sebagai Alternatif Pengganti Antibiotik Terhadap Produktivitas Ternak Unggas - Layyina, Qanita; Husna, Yusfida Mariatul; Firdus, Firdus; Allaily, Allaily (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This study explores the potential of natural feed additives as alternatives to antibiotics in poultry industry, focusing on their mechanisms of action and impacts on productivity. The increasing emphasis on alternative feed additives develops from the global prohibition of antibiotic use in livestock production due to the risk of antimicrobial resistance, which poses a significant threat to public health. Natural feed additives, including phytogenics, organic acids, prebiotics, probiotics, enzymes and their derivatives, have been extensively studied and has demonstrate efficacy comparable to synthetic antibiotics in enhancing poultry performance. These additives have been shown to improve feed intake, enhance digestive efficiency, optimize feed conversion rates, promote growth performance, reduce disease incidence, strengthen immune responses, and control pathogenic microorganisms. The adoption of natural feed additives offers a sustainable and promising solution to mitigate the challenges associated with antibiotic bans in the poultry industry. Comprehensive insights into the types, mechanisms, and effects of these additives are critical for nutritionists, researchers, feed manufactures, and poultry farmers to develop evidence-based strategies for enhancing poultry productivity.